Infant microbiome and factors determining colonization of the gastrointestinal tract and subsequent health consequences - Monika Joanna Stecko; Katarzyna Korabiusz; Agata Wawryków; Anna Fabian Danielewska; Martyna Maciejewska; Inga Janik Fuks; Agnieszka Wilczyńska; Agnieszka Kordek (Kazimierz Wielki University, 2019)
Microbiome is a key element in maintaining health, forming all saprophytic, commensal and parasitic microorganisms that invade the human body. The development of microbiota begins already in the prenatal period, providing the way for further studies on the influence of the course and duration of pregnancy, delivery mode, feeding, exposure to environmental factors and gestational age. Colonization of the gastrointestinal tract of infants is an important aspect of later health. Probiotics and prebiotics can regulate the composition of bacterial flora of the gastrointestinal tract and thus influence the homeostasis of human body.